A companion to Heidegger's Phenomenology of religious life - McGrath, S. J., 1966-; Wierciński, Andrzej. (Elementa, 2010)
In the academic year 1920-1921 at the University of Freiburg, Martin Heidegger gave a series of extraordinary lectures on the phenomenological significance of the religious thought of St. Paul and St. Augustine. The publication of these lectures in 1995 settled a long disputed question, the decisive role played by Christian theology in the development of Heidegger's philosophy. The lectures present a special challenge to readers of Heidegger and theology alike. Experimenting with language and drawing upon a wide range of now obscure authors, Heidegger is finding his way to Being and Time through the labyrinth of his Catholic past and his increasing fascination with Protestant theology. A Companion to Heidegger's Phenomenology of Religious Life is written by an international team of Heidegger specialists.